Trauma masa kecil dan peran inner child dalam pembentukan identitas diri - Astuti, Elly Novie (Maliki Interdisciplinary Journal, 2025)
Childhood trauma is a negative experience that can have long-term impacts on an individual's psychological development, including identity formation. The inner child, which represents the part of oneself that holds childhood memories and emotions, plays a crucial role in shaping thought patterns, self-confidence, and interpersonal relationships. Unresolved trauma can lead to various emotional challenges, such as low self-esteem, difficulties in forming relationships, and mental health disorders like anxiety and depression. Therefore, recognizing and healing the inner child is essential in developing a healthier sense of identity. This healing process can be achieved through self-reflection, journaling, psychological therapy, and adequate social support. By understanding the role of the inner child and the effects of childhood trauma, individuals can enhance their psychological well-being and build a stronger and more stable identity.